POTRET PELAKSANAAN SUHBAT USTÂDZ DAN TÛLUZ ZAMÂN DALAM PEMBELAJARAN BAHASA ARAB DARING - Fatwiah Noor; Ahmad Muradi; Jamal Syarif; Arif Rahman Hakim (Arabi : Journal of Arabic Studies, 2022)
The pandemic has affected various aspects of life, including the field of education by implementing online learning. Limited time and communication between teachers and students in the learning process provide different conditions. This is inversely to the terms proposed by Imam Shafi'i for seeking knowledge. He said there are 6 terms, namely Dzaka’, Hirsh, Ijtihad, Bulghah, Suhbat Ustadz and Tūluz Zaman. The purpose of this paper is to present the concept of Suhbat Ustadz and Tūluz Zaman in online learning at UPB. This paper conveys a quantitative approach with a descriptive qualitative method. Data obtained from the results of a survey from students and teachers. The results show that the concept of Suhbat Ustadz can be seen from the use of teleconference media and other communicative media. While the concept of tūluz zaman can be seen from the unlimited learning time or the availability of time outside of lecture hours.